ENSINO DE LÍNGUAS ESTRANGEIRAS PARA FORMAÇÃO PROFISSIONAL: CONTRIBUIÇÕES DA ABORDAGEM ERGOLÓGICA E DO DIALOGISMO - Freitas, Luciana Maria Almeida de (Intercâmbio, 2010)
This work depicts some theoretical and methodological contributions from Ergology (Schwartz, 1997) and dialogic approach to language (Bakhtin, 2003) to foreign language teaching aiming vocational education. Then, it proposes that an analysis of live work and speeches in work situation can help the teacher build the syllabus.